Interações de alguns ácidos orgânicos com minerais e um latossolo vermelho - Bassan, Cássia Fernanda Domingues [UNESP] (2004)
Certain cultures present especification in the assimilation of some ions, that are or not in available ways in the soil. The minerals have fundamental paper in the presence of those elements that, a lot of times, they are together originating from of the processes of meteorization of the rocks with the decomposition of the organic matter. This work had for objective to study the extraction and/or solubilization of some present chemical elements in the studied minerals and in a red latosoil, for the action of some organic acids produced starting from the decomposition of the matter ligno-cellulousic, through the microbial action, hoping to contribute in some way in the understanding of the mechanisms of fertility of the soil and, consequently, in the mineral nutrition of plants. The used minerals were: manganite [MnO(OH)], hematite (Fe2O3), pirolusite (MnO2), caolinite [Al2Si2O5(OH)4], goethite (HFeO2), bentonite [Na3(Al,Mg)2 2(Si4O10)(OH)2.H2O] e magnetite(Fe3O4), that commonly happen in areas humid intertropicals and a red latosoil, of sandy texture that, it represents more that 20% of the area of the State of Saint Paulo. The minerals and LV were triturated and drizzled in 0,05mm mesh, separately. After having examined with relationship your structure for Difratometric of Ray-X (XRD), 1g of those minerals and LV were conditioned, separately, in glass flasks. Some samples were only treated with distilled water and other with solution 0,02 mol.L-1 of the following acids: acetic, butyric, citric, carbolic, lactic, malic, oxalic, propionic and tannic, separately, for 53 days, with weekly agitations and conditions aerobics. After the digestion of the samples, they were certain the litio concentrations, sodium, potassium, magnesium, calcium, barium, vanadium, cromium, molibdenium, manganese, iron, cobalt, nickel, copper, zinc, cadmium, mercury, boron, aluminum, silicio, tin, lead, match... (Complete abstract click electronic access below)